The miR‐3127‐5p/p‐STAT3 axis up‐regulates PD‐L1 inducing chemoresistance in non‐small‐cell lung cancer. Issue 8 (4th May 2018) - Tang, Dongfang; Zhao, Dandan; Wu, Yun; Yao, Ruyong; Zhou, Lin; Lu, Liming; Gao, Wen; Sun, Yifeng
Abstract: It is less known about miRNA3127‐5p induced up‐regulation of PD‐L1, immune escape and drug resistance caused by increased PD‐L1 in lung cancer. In this study, lentivirus was transduced into lung cancer cells, and quantitative PCR and Western blot were used to detect the expression of PD‐L1. Then immunofluorescence assay was applied to detect autophagy, finally we explored the relationship between PD‐L1 expressions and chemoresistance in patients. As a result, we found that microRNA‐3127‐5p promotes pSTAT3 to induce the expression of PD‐L1; microRNA‐3127‐5p promotes STAT3 phosphorylation through suppressing autophagy, and autophagy could retaine pSTAT3 into the nucleus in miRNA‐3127‐5p knocked cells, and immune escape induced by elevated level of PD‐L1 results in chemoresistance of lung cancer. In conclusion, microRNA‐3127‐5p induces PD‐L1 elevation through regulating pSTAT3 expression. We also demonstrate that immune escape induced by PD‐L1 can be dismissed by corresponding monoclonal antibody.